Analisis Karakteristik Dan Kebutuhan Parkir Di Pasar Tugu Bandar Lampung - Darma, Royadji; Putra, Sasana; Herianto, Dwi (Universitas Lampung, 2019)
The impact of the construction activity centers such as supermarkets, shops,traditional markets and others raises the need for adequate parking spacefacilities to avoid traffic congestion. Parking is an immovable state of a vehiclethat is temporary. One form of parking needs is in Pasar Tugu Bandar Lampung. However, because the existing parking area cannot accommodate the vehicle, a number of vehicles are parked along the road and causes congestion around the market. The purpose of this study was to find out and analyze the parking characteristicsin Pasar Tugu Bandar Lampung and to analyze the capacity and parking spaces needs in Pasar Tugu Bandar Lampung. The results of this study are the maximum accumulation of car is 15 vehicles while motorcycle are 116 vehicles. For the average duration of car is 19.6 minutes while motorcycle are 18.5 minutes. The results for the turnover of car parking are 1.1 vehicles/SRP/hour while motorcycle are 1.2 vehicles/SRP/hour. The maximum capacity of car parking is 31 vehicles/hour while motorcycle are 495 vehicles/hour. The parking space needs for Pasar Tugu Bandar Lampung is as much as 12 SRP for cars and 48 SRP for motorcycles. Keywords: parking, accumulated parking, parking duration, parking turnover, parking capacity, parking needs.